2001
DOI: 10.1038/sj.bmt.1702998
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation for infants with acute leukemia or myelodysplastic syndrome

Abstract: Summary:The objective of this study is to investigate the outcome of children 24 months of age or younger (infants) at the time of allogeneic bone marrow transplantation (BMT) for acute leukemia or myelodysplasia. We analyzed the survival rate, prognostic factors, incidences of late sequelae, and immune reconstitution in 22 infants who underwent allogeneic BMT. The 5-year event-free survival estimate was 45.5% (95% confidence interval (CI), 24.4% to 63.3%). Six patients died of transplant-related complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…22 Our study confirms that reported by others who have demonstrated that phase of disease is the most important factor determining outcome after HC transplantation. 19,22 In our series, the major cause of failure was relapse of disease. Sixteen of 40 patients relapsed after transplantation with the highest relapse incidence occurring in patients with advanced disease at time of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Our study confirms that reported by others who have demonstrated that phase of disease is the most important factor determining outcome after HC transplantation. 19,22 In our series, the major cause of failure was relapse of disease. Sixteen of 40 patients relapsed after transplantation with the highest relapse incidence occurring in patients with advanced disease at time of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] Pui et al 19 retrospectively analyzed cooperative group and individual transplant center data for children with ALL and 11q23 abnormalities, concluding that any type of HSCT was associated with a worse outcome than chemotherapy alone for t(4;11)-positive leukemia. In that study, the EFS rate for the 28 infants who underwent HSCT was only 1973%, which is extremely low compared to our results and those of Sanders et al, 27 who reported a 3-year disease-free survival rate of 42.2% among 40 infants with ALL following HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 102 patients were registered on two consecutive multicenter trials, designated MLL96 and MLL98, between 1995 and2001. Those with a rearranged MLL gene (MLL-R, n ¼ 80) were assigned to receive intensive chemotherapy followed by hematopoietic stem cell transplantation (HSCT), while those with germline MLL (MLL-G, n ¼ 22) were treated with chemotherapy alone.…”
mentioning
confidence: 99%
“…Three MLL-rearranged lines were chosen, because one expressed HLA-C Asn80 alone (MLL-1), another expressed HLA-C Asn80 and HLA-C Lys80 (MLL-2), and the third expressed HLA-C Asn80 , HLA-C Lys80 , and HLA-B Bw4 (MLL-3): MLL-1 (B8, B62, Cw03, Cw07), MLL-2 (B14, B18, Cw08, Cw15), and MLL-3 (B14, B37, Cw06, Cw08). We are interested in studying leukemias with MLL rearrangement because they are common in infant and secondary leukemias that are highly resistant to conventional chemotherapy (25,26) and may benefit from novel therapeutic strategies (27). We investigated the determinants of NK cell cytotoxicity toward these leukemia cells to develop a new treatment approach.…”
Section: Nk Cell Purification and Cytotoxicity Assaymentioning
confidence: 99%